SHAP-IQ: Unified Approximation of any-order Shapley Interactions - Fumagalli, Fabian; Muschalik, Maximilian; Kolpaczki, Patrick; Hüllermeier, Eyke; Hammer, Barbara (Advances in Neural Information Processing Systems (NeurIPS))

On‐Demand Indistinguishable and Entangled Photons Using Tailored Cavity Designs - Bauch, David; Siebert, Dustin; Jöns, Klaus D.; Förstner, Jens; Schumacher, Stefan (Advanced Quantum Technologies)
Abstract The biexciton‐exciton emission cascade commonly used in quantum‐dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work, it focuses on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishability. It achieves this goal by selectively reducing the biexciton lifetime with an optical resonator. It demonstrates that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and twofold degenerate optical modes. The in‐depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum‐dot cavity excitation dynamics with full access to photon properties. It reports non‐trivial dependencies on system parameters and use the predictive power of the combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values, here specifically for the telecom C‐band at 1550 nm.

Continuous-variable quantum optics and resource theory for ultrafast semiconductor spectroscopy [Invited] - Lüders, Carolin; Barkhausen, Franziska; Pukrop, Matthias; Rozas, Elena; Sperling, Jan; Schumacher, Stefan; Aßmann, Marc (Optical Materials Express)
This review examines the use of continuous-variable spectroscopy techniques for investigating quantum coherence and light-matter interactions in semiconductor systems with ultrafast dynamics. Special emphasis is placed on multichannel homodyne detection as a powerful tool to measure the quantum coherence and the full density matrix of a polariton system. Observations, such as coherence times that exceed the nanosecond scale obtained by monitoring the temporal decay of quantum coherence in a polariton condensate, are discussed. Proof-of-concept experiments and numerical simulations that demonstrate the enhanced resourcefulness of the produced system states for modern quantum protocols are assessed. The combination of tailored resource quantifiers and ultrafast spectroscopy techniques that have recently been demonstrated paves the way for future applications of quantum information technologies.

Strain-Induced Indirect-to-Direct Bandgap Transition, Photoluminescence Enhancement, and Linewidth Reduction in Bilayer MoTe2 - Yu, Yueyang; Dong, Chuan-Ding; Binder, Rolf; Schumacher, Stefan; Ning, Cun-Zheng (ACS Nano)

Single-shot spatial instability and electric control of polariton condensates at room temperature - Gao, Ying; Ma, Xuekai; Zhai, Xiaokun; Xing, Chunzi; Gao, Meini; Dai, Haitao; Wu, Hao; Liu, Tong; Ren, Yuan; Wang, Xiao; Pan, Anlian; Hu, Wei; et al. (Physical Review B)

Dynamics-induced charge transfer in semiconducting conjugated polymers - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (Journal of Materials Chemistry C)
Dynamics-induced interchain charge transfer in a polymer aggregate in stack configuration can be understood by single-oligomer polaron energy.

Prozessbegleitende Qualitätssicherung digitaler Ressourcen (OER). Ein Ansatz für die Lehrkräftebildung am Beispiel der Entwicklung eines Onlinekursangebotes. - Schulze, Johanna; Herzig, Bardo (Herausforderung Lehrer:innenbildung. Zeitschrift zur Konzeption, Gestaltung und Diskussion)

“I do not know! but why?” — Local model-agnostic example-based explanations of reject - Artelt, André; Visser, Roelof; Hammer, Barbara (Neurocomputing)

Technical Transparency for Robot Navigation Through AR Visualizations - Dyck, Leonie; Beierling, Helen; Helmert, Robin; Vollmer, Anna-Lisa (Companion of the 2023 ACM/IEEE International Conference on Human-Robot Interaction)

Entrained flow SCR using an in-situ synthesis of catalyst particles for a combined flue gas cleaning system - Beimdiek, Janis; Schmid, Hans-Joachim

Neuartige Flugstrom SCR an online synthetisierten, nanoskaligen Katalysatorpartikeln in einem kombinierten Gasreinigungsprozess (Poster) - Beimdiek, Janis; Schmid, Hans-Joachim

Influence of atomization on the particle formation in spray flame pyrolysis (Presentation) - Massopo, Orlando; Tischendorf, Ricardo; Schmid, Hans-Joachim; Fröde, Fabian; Grenga, Temistocle; Pitsch, Heinz; Bieber, Malte; Reddemann, Manuel; Kneer, Reinhold
Keywords: Flame Stability; Particle Sample Extraction; SMPS; Impurities

Einfluss der Zerstäubung auf diePartikelbildung bei der Sprayflammenpyrolyse (Vortrag) - Massopo, Orlando; Tischendorf, Ricardo; Schmid, Hans-Joachim; Fröde, Fabian; Pitsch, Heinz; Reddemann, Manuel; Grenga, Temistocle; Kneer, Reinhold
Keywords: SpraySyn; Flammenspraypyrolyse; Maghemite Nanopartikel; Gas to particle-Syntheseweg; Probennahme; Verunreinigung

Potassium Titanyl Phosphate Material Engineering Boosting Integrated Optical Source Performance - Eigner, Christof; Padberg, Laura; Quiring, Viktor; Bocchini, Adriana; Santandrea, Matteo; Gerstmann, Uwe; Schmidt, Wolf Gero; Silberhorn, Christine (CLEO 2023)
We study the interaction of gray tracking and DC ionic conductivity in Potassium Titanyl Phosphate (KTiOPO 4 , KTP) and present a novel way to reduce conductivity via a potassium nitrate treatment improving the device quality.

(Photo-)electrochemical reactions on semiconductor surfaces, part B: III-V surfaces–atomic and electronic structure - Hajduk, Andreas; Zare Pour, Mohammad Amin; Paszuk, Agnieszka; Guidat, Margot; Löw, Mario; Ullmann, Fabian; Moritz, Dominik C.; Hofmann, Jan P.; Krischok, Stefan; Runge, Erich; Schmidt, Wolf Gero; Jaegermann, Wolfram; et al. (Encyclopedia of Solid-Liquid Interfaces)

Verben in Szenen. Grammatikgespräche im Sprachvergleich - Topalović, Elvira; Blachut, Alisa (Grundschule Deutsch)

Technology and Civic Virtue - Reijers, Wessel (Philosophy & Technology)
Abstract Today, a major technological trend is the increasing focus on the person: technical systems personalize, customize, and tailor to the person in both beneficial and troubling ways. This trend has moved beyond the realm of commerce and has become a matter of public governance, where systems for citizen risk scoring, predictive policing, and social credit scores proliferate. What these systems have in common is that they may target the person and her ethical and political dispositions, her virtues. Virtue ethics is the most appropriate approach for evaluating the impacts of these new systems, which has translated in a revival of talk about virtue in technology ethics. Yet, the focus on individual dispositions has rightly been criticized for lacking a concern with the political collective and institutional structures. This paper advocates a new direction of research into civic virtue, which is situated in between personal dispositions and structures of governance. First, it surveys the discourse on virtue ethics of technology, emphasizing its neglect of the political dimension of impacts of emerging technologies. Second, it presents a pluralist conception of civic virtue that enables us to scrutinize the impact of technology on civic virtue on three different levels of reciprocal reputation building, the cultivation of internal goods, and excellence in the public sphere. Third, it illustrates the benefits of this conceptions by discussing some paradigmatic examples of emerging technologies that aim to cultivate civic virtue.
Keywords: History and Philosophy of Science; Philosophy

Who Deserves Credit? Banks for the Virtuous in Rural China - von Blomberg, Marianne; Reijers, Wessel (Journal of Contemporary China)

City 5.0: Citizen involvement in the design of future cities - Becker, Jörg; Chasin, Friedrich; Rosemann, Michael; Beverungen, Daniel; Priefer, Jennifer; Brocke, Jan vom; Matzner, Martin; del Rio Ortega, Adela; Resinas, Manuel; Santoro, Flavia; Song, Minseok; Park, Kangah; et al. (Electronic Markets)
Abstract A citizen-centric view is key to channeling technological affordances into the development of future cities in which improvements are made with the quality of citizens’ life in mind. This paper proposes City 5.0 as a new citizen-centric design paradigm for future cities, in which cities can be seen as markets connecting service providers with citizens as consumers. City 5.0 is dedicated to eliminating restrictions that citizens face when utilizing city services. Our design paradigm focuses on smart consumption and extends the technology-centric concept of smart city with a stronger view on citizens’ roadblocks to service usage. Through a series of design workshops, we conceptualized the City 5.0 paradigm and formalized it in a semi-formal model. The applicability of the model is demonstrated using the case of a telemedical service offered by a Spanish public healthcare service provider. The usefulness of the model is validated by qualitative interviews with public organizations involved in the development of technology-based city solutions. Our contribution lies in the advancement of citizen-centric analysis and the development of city solutions for both academic and professional communities.

Explaining the Technical Artifact Quarto!: How Gestures are used in Everyday Explanations - Lohmer, Vivien; Terfloth, Lutz; Kern, Friederike (First International Multimodal Communication Symposium - Book of Abstract)
Keywords: gesture; dual nature; explanations; architecture; relevance